Endosymbiotic and host proteases in the digestive tract of the invasive snail Pomacea canaliculata: diversity, origin and characterization - Godoy, Martín Sergio (2013)
Digestive proteases of the digestive tract of the apple snail Pomacea canaliculata were studied. Luminal protease activity was found in the crop, the style sac and the coiled gut and was significantly higher in the coiled gut. Several protease bands and their apparent molecular weights were identified in both tissue extracts and luminal contents by gel zymography: (1) a 125 kDa protease in salivary gland extracts and in the crop content; (2) a 30 kDa protease throughout all studied luminal contents and in extracts of the midgut gland and of the endosymbionts isolated from this gland; (3) two proteases of 145 and 198 kDa in the coiled gut content. All these proteases were inhibited by aprotinin, a serine-protease inhibitor, and showed maximum activity between 30C and 35C and pH between 8.5 and 9.5. Tissue L-alanine-N-aminopeptidase activity was determined in the wall of the crop, the style sac and the coiled gut and was significantly higher in the coiled gut. Our findings show that protein digestion in P. canaliculata is carried out through a battery of diverse proteases originated from the salivary glands and the endosymbionts lodged in the midgut gland and by proteases of uncertain origin that occur in the coiled gut lumen.